Evaluation of dentinal bridge formation after pulpotomy with white Portland cement and white MTA in primary anterior teeth: radiographic comparative study (Journal of Hama University, 2022)
Studies in the city of Damascus showed severely prevalence of early childhood caries (ECC), especially in the primary anterior teeth. Because of the small size of these teeth, endodontic exposures occur early, and in this case, the traditional treatment is root canal treatment. Therefore, the aim of this current clinical trial was to evaluate radiologically the rate of dentin bridge formation in vital primary anterior teeth after pulpotomy using white Portland cement (WPC) in comparison with White MTA.The study sample consisted of 60 primary anterior teeth in 23 healthy children aged 4 to9 year-old, and the studied teeth were randomly divided into one of the two groups, WPC or WMTA. Radiological evaluation of dentin bridge formation was done after 3,6,12 months.The rate of dentin bridge formation after 3 months was 83.3% and 80% for WPC and WMTA, respectively. While the rate of dentinal bridge formation after 6 and 12 months was 93.3% and 90% for WPC and WMTA, respectively. No statistically significant differences were observed between the two groups during the three time periods.Thus, pulpotomy with WMTA or WPC is an effective treatment for asymptomatic primary anterior teeth. PC can be considered a good alternative to the MTA in pulpotomy primary anterior teeth.